Oxidation of propane to acrylic acid and acetic acid over alkaline earth-doped Mo-V-Sb-O-x catalysts - Chaudhari, Chandan S.; Sable, Shailesh S.; Gurav, Hanumant; Kelkar, Ashutosh A.; Rane, Vilas H. (Journal of Natural Gas Chemistry, 2010)
Alkaline earth metal (Mg, Ca, Sr and Ba)-doped Mo-V-Sb-O-x catalysts, prepared by a dry-up method, have been investigated for their catalytic performance in the oxidation of propane under different reaction conditions. The catalysts have been characterized by N-2 adsorption-desorption, temperature-programmed desorption (TPD) of NH3, SEM and XRD. Influence of water vapor on the catalytic performance, particularly on the selectivities to acetic acid and acrylic acid, has also been studied. The selectivity to acrylic acid was improved significantly by the doping of alkaline earth metals to Mo-V-Sb-O-x catalysts. The surface acidic sites of the catalyst decreased with the doping of the catalyst with alkaline earth metals, which ultimately was found to be beneficial for obtaining high selectivity to acrylic acid. The catalytic activity and product selectivities were found to be influenced by the reaction temperature, C3H8/O-2 ratio and space velocity. A significant improvement in the selectivity to acrylic acid has also been observed by the addition of water vapor in the feed of propane and oxygen in the oxidation of propane.
Keywords: Acetic acid; acrylic acid; alkaline earth doped Mo-V-Sb-O-x catalysts; oxidation of propane; Surface acidity

Uncatalyzed synthesis of thiomorpholide using polyethylene glycol as green reaction media - Gawande, Shrikant S.; Bandgar, Babasaheb P.; Kadam, Prasad D.; Sable, Shailesh S. (Green Chemistry Letters and Reviews, 2010)
Polyethylene glycol-600 was used as an efficient and recyclable solvent for the one-pot three component condensation reactions of aryl alkyl ketones, sulfur, and morpholine to produce the corresponding thiomorpholide. This protocol has advantages of high yields, short reaction times, mild reaction conditions, minimal environmental pollution, and simple work up procedure. [GRAPHICS] .
Keywords: polyethylene glycol-600; Sulfur; thiomorpholide; Willgerodt-Kindler reaction

Catalytic ozonation of clofibric acid over copper-based catalysts: in situ ATR-IR studies - Sable, Shailesh S.; Ghute, P. P.; Fakhrnasova, D.; Mane, R. B.; Rode, Chandrashekhar V.; Medina, F.; Contreras, S. (Applied Catalysis B-Environmental, 2017)
The current study describes the catalytic ozonation of clofibric acid (CFA) under ambient conditions using copper oxide catalysts synthesized by different methods. The objective of this study is to provide novel catalysts and reaction mechanism for the degradation of emerging pharmaceutical compounds in aqueous solution. Among the various Cu catalysts screened in this study, the Cut-Ali oxide catalyst showed an excellent activity and stability in the degradation and mineralization of CFA. In situ attenuated total reflection IR (ATR-IR) spectroscopy was used to examine the interaction of ozone with the active sites of the catalyst in presence of water and to investigate the possible catalytic mechanism. The presence of Lewis acid sites in the Cut-Ali catalyst increased the amount of chemisorbed water enhancing stronger interaction of ozone to form surface activated species, resulting in higher catalytic activity. The results obtained from in-situ ATR-IR study indicate that surface hydroxyl groups and Lewis acid sites are responsible for promoting the generation of hydroxyl radicals (OHS) from aqueous ozone. (C) 2017 Elsevier B.V. All rights reserved.